Oral histories from the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
At the desert's edge - oral histories from the Sahel edited by Nigel Cross and Rhiannon Barker 248pp ISBN 1 870670 26 4 Pbk UKL12.95 Panos Publications Ltd 9 White Lion Street London N1 9PD, UK